The Role of Supply Chain Process in the Goal Attainment among United Nations Missions in Conflict Situations. A Case Study of United Nations Mission in South Sudan (UNMISS). - Emuria Patel; Ochatum Nathan; Okwii Moses (International Journal of Supply Chain Management, 2018)
The need for organizations to have successful supply chain management so that, the goals of these organizations are attained is uncontested. However, the UN peacekeeping missions have had challenges ensuring the effectiveness of the supply chain. Therefore, this study sought to establish the effect of supply chain processes on the attainment of goals in the UN peacekeeping missions. Supply chain processes involved value creation, integration of key business processes and collaboration of the team members and other partners. The theoretical underpinning of the study was based on the Systems theory of Bertalanffy (1950) to view UNMISS as a system with supply chain management. The study adopted a descriptive case study research design. Descriptively, the study employed questionnaire and document reviews in the data collection process while analysis and presentation of findings involved the use of tables, graphs and charts. The study established that the supply chain processes are very important in the attainment of UN peacekeeping mission goals in South Sudan. These processes in terms of value creation, integration of key business processes and collaboration amongst stakeholders ensure that there is value for money through full utilization of resources, obedience of decisions made by the UN secretariat, employment of competent staff training and continued flow of their activities. The model results showed that value creation has a positive significant effect on the attainment of goals in the UN peacekeeping mission in South Sudan. The researchers recommended that the need to embrace technology is paramount when it comes to supply chain management and attainment of goals by the UN peacekeeping missions.